2006
DOI: 10.1128/aac.00329-06
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Open-Label, Comparative Study of Piperacillin-Tazobactam Administered by Continuous Infusion versus Intermittent Infusion for Treatment of Hospitalized Patients with Complicated Intra-Abdominal Infection

Abstract: The purpose of this randomized, multicenter, open-label study was to compare the continuous infusion of piperacillin-tazobactam with the standard intermittent infusion in 262 hospitalized patients with complicated intra-abdominal infections. Within 1 day of surgical intervention, eligible patients were randomized (1:1) to piperacillin-tazobactam 12 g/1.5 g administered continuously over 24 h or 3 g/0.375 g administered over 30 min intermittently every 6 h for 4 to 14 days. The demographics of the patients in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
134
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(143 citation statements)
references
References 28 publications
4
134
0
5
Order By: Relevance
“…Furthermore, as expected, we found that more frequent intermittent piperacillin doses produced a higher PTA across all BMI categories. We also found that piperacillin extended and continuous infusions greatly improved the PTA (an MIC up to at least 8 mg/liter) in the presence of different BMIs and measured CL CR s. These data support those of other investigators (19)(20)(21), which suggest that extended and continuous infusions can normalize any effects of altered weight and renal function on achievement of therapeutic concentrations.…”
Section: Resultssupporting
confidence: 89%
“…Furthermore, as expected, we found that more frequent intermittent piperacillin doses produced a higher PTA across all BMI categories. We also found that piperacillin extended and continuous infusions greatly improved the PTA (an MIC up to at least 8 mg/liter) in the presence of different BMIs and measured CL CR s. These data support those of other investigators (19)(20)(21), which suggest that extended and continuous infusions can normalize any effects of altered weight and renal function on achievement of therapeutic concentrations.…”
Section: Resultssupporting
confidence: 89%
“…Currently, we do not know whether different PIP-TZ administration modalities (13,14,16) or higher PIP-TZ doses can improve the PIP-TZ penetration into PJ. Knowledge of the elimination of antibiotics with the PJ is important for the efficacy of therapy, since the amount of drug secreted into the PJ is an indicator of greater concentrations in the pancreatic tissue.…”
mentioning
confidence: 99%
“…We also found that piperacillin extended and continuous infusion greatly improved PTA (MIC up to at least 8 mg/L) in the presence of different BMIs and measured CLCR. These data support others 60,144,145 , which suggest that extended and continuous infusions can normalise any effects of altered weight and renal function on achievement of therapeutic concentrations.…”
Section: Key Findingssupporting
confidence: 87%